Plants used traditionally as antimalarials in Latin America: Mining the tree of life for potential new medicines. (28th October 2021) - Milliken, William; Walker, Barnaby E.; Howes, Melanie-Jayne R.; Forest, Félix; Nic Lughadha, Eimear
Abstract: Ethnopharmacological relevance: Malaria remains a serious and challenging disease. Traditional antimalarial medicines are largely based on plants, and ethnopharmacological research has inspired the development of antimalarial pharmaceuticals such as artemisinin. Antimalarial drug resistance is an increasing problem in Plasmodium species, and new therapeutic strategies to combat malaria are needed. Although the number of malaria cases has been decreasing in Latin America, malaria remains a significant threat in many regions. Local people in Latin America have been using numerous plant species to treat malaria, some of which have been scientifically studied, but many others have not. Aim of the study: Our principal objective is to harness ethnobotanical data on species used traditionally to treat malaria, combined with phylogenetic approaches, to understand how ethnobotany could help identify plant genera as potential sources of new medicines. Materials and methods: Plants used to treat malaria in Latin America were compiled from published and grey literature, unpublished data, and herbarium specimens. Initial assessment of potentially important species/genera/families included compiling the number of species used within the genus, the number of use reports per genus and species, and the geographic distribution of their use. The analysis of taxonomic distribution of species reported as antimalarial in Latin America (excluding the Southern Cone) was conducted, to determine which genera and families with reputed antimalarial properties are over-represented, and phylogenetic analyses were performed to identify if there was evidence for antimalarial species being dispersed/clustered throughout the tree or at its tips. This approach enabled 'hot-nodes' in certain families to be identified, to predict new genera with potential antimalarial properties. Results: Over 1000 plant species have been used to treat malaria in Latin America, of which over 600 species were cited only once. The genera with the highest number of antimalarial species were Aspidosperma, Solanum, Piper, Croton and Aristolochia . In terms of geographic distribution, the most widely used genera were Aspidosperma, Momordica, Cinchona, Senna and Stachytarpheta . Significant phylogenetic signal was detected in the distribution of native species used for malaria, analysed in a genus-level phylogenetic framework. The eudicot and magnoliidae lineages were over-represented, while monocots were not. Conclusion: Analysis of ethnobotanical use reports in a phylogenetic framework reveals the existence of hot nodes for malaria across the Latin American flora. We demonstrate how species and genera currently lacking such reports could be pinpointed as of potential interest based on their evolutionary history. Extending this approach to other regions of the world and other diseases could accelerate the discovery of novel medicines and enhance healthcare in areas where new therapeutic strategies are needed. Graphical abstract: Image 1 Highlights: First comprehensive dataset of plants used traditionally for malaria in Latin America. Significant phylogenetic signal in the distribution of species reported as antimalarial. Over-representation of species can originate from deep nodes in the Tree of Life. Identification of genera not currently used could target the search for novel antimalarials. Support for documenting traditional medicinal knowledge for global healthcare.